2023
DOI: 10.3390/ijms24086931
|View full text |Cite
|
Sign up to set email alerts
|

A New One-Tube Reaction Assay for the Universal Determination of Sweet Cherry (Prunus avium L.) Self-(In)Compatible MGST- and S-Alleles Using Capillary Fragment Analysis

Abstract: The sweet cherry plant (Prunus avium L.) is primarily self-incompatible, with so-called S-alleles responsible for the inability of flowers to be pollinated not only by their own pollen grains but also by pollen from other cherries having the same S-alleles. This characteristic has wide-ranging impacts on commercial growing, harvesting, and breeding. However, mutations in S-alleles as well as changes in the expression of M locus-encoded glutathione-S-transferase (MGST) can lead to complete or partial self-compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The reference set is structured in such a way that each S-haplotype is included at least once (Table 2). Further genotypes can be continuously added to this reference set to fill in missing or newly identified S-alleles, such as the recently published S 54 allele from the variety 'Techlovicka' (Cmejlova et al, 2023).…”
Section: Reference Genotypes and Amplicondeep Sequencing For S-allele...mentioning
confidence: 99%
See 4 more Smart Citations
“…The reference set is structured in such a way that each S-haplotype is included at least once (Table 2). Further genotypes can be continuously added to this reference set to fill in missing or newly identified S-alleles, such as the recently published S 54 allele from the variety 'Techlovicka' (Cmejlova et al, 2023).…”
Section: Reference Genotypes and Amplicondeep Sequencing For S-allele...mentioning
confidence: 99%
“…Furthermore, the marker PaConsI-F/R2 is not suitable for the amplification from the S 13 allele as no PCR product or eventually a SSR like trace peak is produced, which has been already reported (Sonneveld et al, 2006;Marchese et al, 2010;Lisek et al, 2015) and confirmed in this work. Although the primer binding sites are present in S 13 , a short highly variable tandem repeat, presenting up to 25 (AT) repeats in P. avium and up to 38 in P. cerasus (Marchese et al, 2010) in the amplified region probably inhibits the PCR, as already discussed by Cmejlova et al (2023). For three genotypes of the Caucasian collection, the allele S 13 was assigned on the basis that in these only one PCR product was detected and a diploid, selfincompatible genotype was assumed.…”
Section: Limitations Of S-allele Genotyping Using the Universal Marke...mentioning
confidence: 99%
See 3 more Smart Citations